1994
DOI: 10.1038/371806a0
|View full text |Cite
|
Sign up to set email alerts
|

The Trithorax-like gene encodes the Drosophila GAGA factor

Abstract: Little is known about the way higher-order chromatin structure influences gene expression and chromosome topology in general. Genetic analysis in Drosophila has led to the discovery of two classes of genes, the regulators of homeotic genes and the modifiers of position-effect variegation, which seem to be good candidates for encoding some of the factors regulating chromatin functions. The Trithorax-like gene we described here is required for the normal expression of the homeotic genes and is a modifier of posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
320
3
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(339 citation statements)
references
References 25 publications
11
320
3
5
Order By: Relevance
“…Possible involvement of GAGA factors in enhancement of striped en expression GAGA factors or Trl proteins are a set of DNA-binding protein isomers encoded by the Trl gene (Farkas et al 1994;Benyajati et al 1997). They bind strongly to GAGAG and weakly to GAG (O'Brien et al 1995;Omichinski et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible involvement of GAGA factors in enhancement of striped en expression GAGA factors or Trl proteins are a set of DNA-binding protein isomers encoded by the Trl gene (Farkas et al 1994;Benyajati et al 1997). They bind strongly to GAGAG and weakly to GAG (O'Brien et al 1995;Omichinski et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The pentamer GAGAG (CTCTC), situated between TATA and Inr is required for insulation at the even-skipped (eve) locus (Read et al 1990). Mutations in the pentamer and reduction in GAGAG-binding proteins termed GAGA factors (for review, see Granok et al 1995) or Trithorax-like (Trl; Farkas et al 1994), were found to prevent the transcriptional insulation of eve neighbours .…”
Section: Introductionmentioning
confidence: 99%
“…Although only BCL6-mediated-transcriptional silencing has been reported to date, the implication of a single POK protein in various aspects of DNA metabolism is now increasingly clear. This is strikingly exemplified by the well-studied Drosophila GAGA POK protein that acts in anti-repression and nucleosome disruption, mediates stable repression, counteracts heterochromatinmediated repression, modulates enhancer-promoter communication, and is required for chromosome condensation and separation (Bhat et al, 1996;Busturia et al, 2001;Croston et al, 1991;Farkas et al, 1994;Horard et al, 2000;Mahmoudi et al, 2002;Mishra et al, 2001;Ohtsuki and Levine, 1998;Tsukiyama et al, 1994;Xiao et al, 2001). All these activities are likely mechanistically linked and depend on a "basic" property shared by other POK proteins, namely the ability to self-aggregate and bring together "distant" pieces of DNA (Americo et al, 2002;Katsani et al, 1999;Mahmoudi et al, 2002;West et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, GAGA elements are known to be natural targets for GAF proteins [52]. GAF protein is a member of the trithorax group (trxG) proteins [53]. The Polycomb group (PcG) and trxG proteins are required for determining the state of expression of developmental regulators, such as homeotic genes [54].…”
Section: Discussionmentioning
confidence: 99%